Giant Merkel cell carcinoma: report of an atypical case - Ana Carolina Cechin de Mello; Rogerio Nabor Kondo; Betina Samesima e Singh; Airton dos Santos Gon (Surgical & Cosmetic Dermatology)
Merkel cell carcinoma is a rare and aggressive cutaneous neuroendocrine cancer that occurs on sun-damaged skin in older White patients. It typically manifests as a solitary plaque or nodule in the head and neck region. We report an unusual presentation of Merkel cell carcinoma in a black patient who simultaneously developed two primary tumors located in the trunk region.